The effect of budgetary participation on the performance of officials with locus of control, job satisfaction, and relevant job information as mediating variables: An empirical study at regional work unit (SKPD) in Palu - Chaeranti Muldayani Dewi; Gugus Irianto; Rosidi - (Journal of Economics, Business, and Accountancy Ventura, 2016)
The objective of this study is to analyze the effect of budgetary participation on the performance of the officials of Regional Work Units (SKPD) with locus of control, job satisfaction, and relevant job information as mediating variables. The study was done on SKPD in Palu by survey using questionnaires. The sample consists of 40 people selected by using purposive sampling technique. Data were analyzed using multiple regressions and moderating regression analysis (MRA). The results show that budgetary participation significantly affects the performance of the SKPD in Palu. Locus of control (LoC) as a moderating variable does not strengthen the effect of budgetary participation on the performance of officials. Job satisfaction can mod-erate the effect of budgetary participation on the performance of officials. The results also reveal that relevant job information can moderate the performance of SKPD in Palu. Thus, this study proves that budgetary participation supported by job satisfac-tion and relevant job information can build the performance of SKPD in Palu.